The Influence of Management and Teacher Quality on Madrasah Performance Based on Accreditation Instrument for Education Unit (IASP) 2020 in West Sulawesi - Kamus, Kamus; Mas’ud, Bulqia; Saddang, Muhammad; Abdurrahman, Abdurrahman; Azwar, Azwar; Kurniawan, Rahmat (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study examines the factors behind the low performance of madrasahs in West Sulawesi based on IASP 2020, analyzing root causes and assessing the impact of school management and teacher quality on educational outcomes. Using a mixed-methods approach, the study integrates quantitative and qualitative analyses. The quantitative phase examines secondary data from the National Accreditation Board, focusing on school leadership, teacher quality, teaching effectiveness, and student achievement. Correlation and regression analyses are employed to determine significant influences on madrasa performance. In the qualitative phase, 18 low-performing madrasahs are selected for focus group discussions (FGDs) and semi-structured interviews with key stakeholders, including school administrators, teachers, students, and education experts. Thematic analysis identifies recurring patterns, with findings triangulated against quantitative data for reliability and validity. The population in this study consists of 62 madrasahs targeted for accreditation in West Sulawesi in 2023. A sample of 36 madrasahs accredited with a C rating was then selected. The results highlight that school management and teacher quality are critical but often constrained by inadequate planning, inefficient resource allocation, and limited professional development. Additionally, learning processes and student quality mediate accreditation outcomes. The study underscores the necessity of comprehensive management reforms and targeted teacher training programs to enhance madrasa performance. These findings provide valuable insights for policymakers, educators, and stakeholders, offering evidence-based strategies to improve Islamic education quality in West Sulawesi.